Cells diversify transmembrane signaling through the controlled chaos of protein disorder - Sigalov, Alexander B (Landes Bioscience, 2011)
Cell surface receptors function to transduce signals across the cell membrane leading to a variety of biologic responses. Structurally, these integral proteins can be classified into two main families, depending on whether extracellular ligand-binding and intracellular signaling domains are located on the same protein chain (single-chain receptors, SRs) or on separate subunits (multichain receptors, MRs). Since most MRs are immune receptors, they are all commonly referred to as multi-chain immune recognition receptors (MIRRs). Recent studies reveal that, in contrast to well-structured signaling domains of SRs, those of MIRRs represent intrinsically disordered regions, the regions that lack a well-defined three-dimensional structure under physiological conditions. Why did nature separate recognition and signaling functions of MIRRs? Why for MIRRs did nature select to provide highly specific signaling through the chaos of protein disorder? What mechanisms could control this chaos in the process of transmembrane signal transduction to provide the specificity and diversity of the immune response? Here, I summarize recent findings that may not only shed light on these and other questions but also add significantly to our understanding of receptor signaling, a fundamental process that plays a critical role in health and disease.